Pola Penggunaan Antihipertensi pada Pasien Diabetes Mellitus Tipe 2 di Poli Penyakit Dalam RS Bhayangkara Surabaya - Pramadani, Yana; Hasmono, Didik; Kasih, Elisabeth; Hartono, Ruddy (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2018)
Diabetes mellitus (DM) is a metabolic disease characterized by symptoms of hyperglycemia. This disease can be caused due to abnormalities in insulin secretion, insulin action or both. Management of diabetes mellitus in general is to improve the quality of life of people with diabetes, namely to eliminate complaints of diabetes mellitus, improve quality of life, and reduce the risk of acute complications; to achieve this goal their blood pressure must be controlled using antihypertensive therapy. The purpose of this study was to examine the pattern of antihypertensive drug use related to the type, dose, and frequency of administration in reducing blood pressure in patients with type 2 diabetes mellitus in the internal medicine clinic of Bhayangkara Hospital Surabaya. The method of this study was observational because researchers did not provide treatment directly to patients. Data were collected retrospectively between August 1 and September 15, 2015. The results showed 80 patients (48%) used single therapy and 86 patients (52%) used combination therapy. The antihypertensive drug that is often used as a single therapy is valsartan (1x80 mg) given orally in 16 patients (20%) and as a combination is valsartan (1x80 mg) + amlodipine (1x10 mg).